النفايات المنزلية وأثرها على البيئة في مدينة الصدر وامكانية الاستفادة منها اقتصاديا - الخزاعي , م. د. ماجدة جاسم; . د. خالد اكبر عبدالله (Thi Qar Arts Journal, 2021)
The problem of waste and recycling methods is great importance to spot light and attention to it because it is one of the sources of pollution. The research focused on the mechanism of waste collection in Sadr City and the damage resulting from it and the possibilities available for recycling and benefiting from it. The research shows that the method of collection of household waste in the study area is a traditional and useless method. There is no sorting process for the solid waste generated inside the city where collection vehicles collect waste from residential units, administrative institutions - commercial - industrial areas transfer them to landfill sites without benefiting from these wastes. During the recycling process. The amount of money spent annually on the process of collection, transport and landfill to (11.556.000000) Iraqi dinars, however, the problem of pollution resulting from it has not been properly resolved. The waste components can be utilized through classification and recycling. This process will provide a lot of materials, including organic fertilizers and animal feed as well as the energy used for the production of raw materials. This process will reduce transport costs as well as the volume of waste arriving at the site Landfill